2022
DOI: 10.26508/lsa.202101145
|View full text |Cite
|
Sign up to set email alerts
|

SMN-deficient cells exhibit increased ribosomal DNA damage

Abstract: Spinal muscular atrophy, the leading genetic cause of infant mortality, is a motor neuron disease caused by low levels of survival motor neuron (SMN) protein. SMN is a multifunctional protein that is implicated in numerous cytoplasmic and nuclear processes. Recently, increasing attention is being paid to the role of SMN in the maintenance of DNA integrity. DNA damage and genome instability have been linked to a range of neurodegenerative diseases. The ribosomal DNA (rDNA) represents a particularly unstable loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Our results show a newly discovered SMN function in nucleolar homeostasis and may directly impact the life and well-being of SMA patients 33 . In fact, in cells and motoneurons of SMA patients, exogenous and endogenous DNA damage might progressively and lastingly disrupt nucleolar structure and disturb ribosome biogenesis leading to perturbed protein translation 34 . This defect may contribute to the neurodegenerative phenotype of SMA motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show a newly discovered SMN function in nucleolar homeostasis and may directly impact the life and well-being of SMA patients 33 . In fact, in cells and motoneurons of SMA patients, exogenous and endogenous DNA damage might progressively and lastingly disrupt nucleolar structure and disturb ribosome biogenesis leading to perturbed protein translation 34 . This defect may contribute to the neurodegenerative phenotype of SMA motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, the concept that SMN orchestrates a ribosome-centric platform for regulating mRNA translation offers a distinctive framework for expanding our understanding of the molecular mechanisms underlying the global translational defects observed in multiple models of SMA [ 2 , 10 , 17 , 19 , 60 ].…”
Section: Smn Functions As a Ribosome-associated Protein Acting As A H...mentioning
confidence: 99%
“…SMN plays fundamental roles in the biogenesis of ribonucleic particles [ 5–7 ], pre-mRNA splicing [ 8 ], and RNA metabolism at large [ 9 ]. In addition, SMN deficiency is likely linked to rDNA damage and impaired rRNA synthesis [ 10 ]. However, abnormalities in these functions observed in SMA cannot fully recapitulate the disease pathogenesis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings include: the presence of P53-mediated DNA damage via dysregulation of P53 repressors Mdm2 and Mdm4 (Jangi et al, 2017 ; Simon et al, 2017 ; Van Alstyne et al, 2018 ), R-loop accumulation and R-loop-mediated DNA damage (Zhao et al, 2016 ; Jangi et al, 2017 ; Kannan et al, 2018 ), rescue of R-loop-mediated DNA damage (Kannan et al, 2020 ) and defects in the assembly of R-loop resolution complexes (RLRC) as a cause of nuclear/nucleolar R-loop accumulation and DNA damage in SMA (Kannan et al, 2022 ). A recent study shows that the knockdown of DDX21 may contribute to nucleolar R-loop accumulation and ribosomal DNA damage in SMN-deficient cells (Karyka et al, 2022 ). A timeline for the involvement of DNA damage and impaired DNA repair in SMA pathogenesis is shown in Figure 2 .…”
Section: Dna Damage In Smamentioning
confidence: 99%
“…A recent study identified nucleolar DEAD/H BOX RNA helicase 21 (DDX21) downregulation in SMA patient-derived IPSC motor neurons. DDX21 knockdown results in R-loop accumulation in the nucleolus, which may be a cause of ribosomal DNA damage in SMN-deficient cells (Karyka et al, 2022 ). Extensive mitochondrial pathology has also been reported in SMA, including mitochondrial DNA (mtDNA) damage, raising the question of whether mtDNA damage in SMA is R-loop mediated (Miller et al, 2016 ; James et al, 2021 ).…”
Section: R-loop-mediated Dna Damage In Smamentioning
confidence: 99%